PENGAJARAN SASTRA BAHASA JERMAN DI SEKOLAH MENENGAH ATAS (SMA) - Nurfadilla, Nurfadilla; Rijal, Syamsu; Usman, Misnawaty (Universitas Negeri Makassar, 2020)
Abstract. This research is a descriptive qualitative research. It aims to obtain information on the relevant themes and types of literary works taught in school. Data seurcesof this research were primary and secondary data . Data collecting, the researcher used library technique. The data obtained were then analyzed using the heuristic and hermeneutic reading methods. The findings show that the relevant themes of German literary work that can be used in teaching are family, daily life, divinity, nature, and health by paying attention to the level of students' language skill. As for the types of German literary works based on the findings, the relevant types are Lyrics and Short Stories.